High expression of SHP2 predicts a promising prognosis in colorectal cancer - Xibo Liu; Mengyao Li; Lirong Chen; Fei Wen; Shu Zheng; Weiting Ge (Indian Journal of Pathology and Microbiology)
Background: Src homology 2 domain-containing phosphatase 2 (SHP2) is hyper-activated in some solid tumors. Previous findings suggest that the expression of SHP2 in colorectal cancer (CRC) may be associated with prognosis. However, validation with large sample data is lacking. Materials and Methods: Tissue microarrays containing 860 CRCs and 197 mucosal tissues adjacent to the tumors were constructed. Immunohistochemistry was used to evaluate the expression of SHP2. Differences between SHP2 expression and clinicopathological parameters were evaluated. Kaplan–Meier survival curves and log-rank tests were used to analyze the relationships between SHP2 expression and the overall survival of patients. A Cox proportional hazard regression model was used for univariate and multivariate analyses of prognostic factors. Results: SHP2 expression in CRCs tissues was significantly higher than those in adjacent mucosal tissues (P < 0.001). SHP2 expression was related to tumor differentiation, depth of invasion, distant metastasis, vascular tumor thrombus, lymph node metastasis, and TNM classification (P < 0.05). The prognosis of the high-expression group of SHP2 was significantly better than that of the low-expression group (P = 0.008). Univariate analysis showed that the expression of SHP2 was a prognostic factor for CRC (P = 0.008). Multivariate analysis demonstrated that SHP2 remained an independent prognostic factor for CRC (P = 0.033). Conclusion: The expression of SHP2 was significantly higher in CRC tissues than in adjacent normal tissues. High expression of SHP2 was associated with a promising outcome, suggesting that SHP2 may be a favorable prognostic indicator of CRC.